Prediction of Coronary Angiographic Features in Different Clinical Presentations of Unstable Angina (Bangladesh Journal of Medicine, 2014)
Background: The clinical syndrome of unstable angina can be manifested in different ways. There are three principal presentations of unstable angina like prolonged angina at rest, new onset angina and accelerated angina. Clinical characteristics can be correlated with morphological features of coronary artery assessed by coronary angiogram. Objective: The prospective observational study was conducted to compare angiographic findings with different clinical presentations of unstable angina. Methods: The study was carried out in the Department of Cardiology of Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2005 to December 2006. Total 75 patients with different clinical scenarios of unstable angina were included in this study. Results: Patients with rest angina showed triple vessel disease in comparison to other groups (40%vs.8% and 24%). Regarding lesion characteristic, more complex lesions(type B and C) are common in cases with rest angina in comparison to new onset angina and accelerated angina.(76% vs.48% and 40%) Vessel score and stenosis score are also high in rest angina in comparison to other types. (2.53± 0.76vs. 1.56±0.92). Patients with rest angina also present more proximal and osteal lesions. The incidence of long intracoronary lesions were high in patients with rest angina (20% vs.4%) Conclusion: This study shows that coronary angiographic morphology was not same in unstable angina patients who presented with different clinical scenario. So, complexity of angiographic lesion morphology can be predicted from clinical presentation. DOI: http://dx.doi.org/10.3329/bjmed.v24i2.18698 Bangladesh J Medicine 2013; 24 : 45-50